Structure Activity Relationship Studies of a Novel Series of Anthrax Lethal Factor Inhibitors - Johnson, Sherida L. (2009)
We report on the identification of a novel small molecule inhibitor of anthrax lethal factor using a high-throughput screening approach. Guided by molecular docking studies, we carried out structure activity relationship (SAR) studies and evaluated activity and selectivity of most promising compounds in in vitro enzyme inhibition assays and cellular assays. Selected compounds were further analyzed for their in vitro ADME properties, which allowed us to select two compounds for further preliminary in vivo efficacy studies. The data provided represents the basis for further pharmacology and medicinal chemistry optimizations that could result in novel anti-Anthrax therapies.